2013
DOI: 10.1186/1477-7525-11-198
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life of children with rheumatic heart diseases: reliability of the Brazilian version of the pediatric quality of life inventory™ cardiac module scale

Abstract: BackgroundThis study aimed to translate the ‘Pediatric Quality of Life Inventory™ (PedsQL™ 3.0) Cardiac Module’ into Portuguese, adapt it to Brazilian culture, and assess its psychometric properties (validity and reproducibility), and to calculate health-related quality of life scores on the PedsQL 4.0 and PedsQL™ 3.0 Cardiac Module Scales for a group of patients 5 to 18 years old with rheumatic heart disease.MethodsThe methods suggested by the authors of the original version of the questionnaire included 1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
(62 reference statements)
4
12
2
1
Order By: Relevance
“…Cronbach’s alpha coefficients exceeded 0.7 in the total scale and every dimension in both parent proxy reports and child self-reports, indicating good reliability. However, these values were higher than those described in previous reports assessing patients with a wide range of diseases in other countries, with values generally over 0.7 but around 0.6 for some dimensions [ 13 , 16 , 18 , 21 ].…”
Section: Discussioncontrasting
confidence: 78%
“…Cronbach’s alpha coefficients exceeded 0.7 in the total scale and every dimension in both parent proxy reports and child self-reports, indicating good reliability. However, these values were higher than those described in previous reports assessing patients with a wide range of diseases in other countries, with values generally over 0.7 but around 0.6 for some dimensions [ 13 , 16 , 18 , 21 ].…”
Section: Discussioncontrasting
confidence: 78%
“…According to Ferguson and Kovacs, 33 some aspects contribute to a poor quality of life, including low social support, emotional instability, poor health, and low exercise tolerance. Quality of life scores were around 70%, corroborating the findings by Moraes et al, 34 who evaluated the same population profile aiming to validate the heart module of PedsQL for Brazil. Although there are no cutoff points described in the literature, these authors considered that these levels correspond to a lower quality of life, as per the study by Klatchoian et al, 17 who, found a score of 72% for children with chronic rheumatic diseases compared to healthy ones, with scores of 88%, while validating the general PedsQL for Brazil - a significant difference.…”
Section: Discussionsupporting
confidence: 86%
“…In Sao Paulo, Brazil, a Portuguese translation of the Pediatric Quality of Life Inventory core and cardiac module was used to investigate the quality of life of 109 young people with RHD and their parents 241 . Results indicated global impairment of quality of life in physical, emotional, social, school and psychosocial domains.…”
Section: Quality Of Lifementioning
confidence: 99%